The Implementation Multimedia As A Teaching Method To Improve The Speaking Ability Of Tenth Grade At Sma Negeri 5 Pematang Siantar - Benarita Purba; Semaria Eva Elita Girsang; Roymantini Sihite (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2023)
The objective of this research was to find out the using multimedia as a teaching method improve the speaking ability of tenth grade at SMA Negeri 5 Pematang Siantar. This research was conducted at SMA Negeri 5 Pematang Siantar . This research used quantitative with true experimental method. Population of this research was grade tenth with 10 classes which consists of 360 students and the sample of this research was 36 students in one class. The technique of collecting data was pre-test and posttest. The technique of analyzing data by using SPSS version 26.0. The result ofresearch was (Tcounted = 65,000 > Ttable = 1,689) at the significance level α =0.05 with the degrees of freedom (df) = (36-1=35) for each class so the degrees of freedom is 70. Ho( there is no significant effect of using multimedia on student’s speaking ability ) is rejected and Ha (there is a significant effect of using multimedia on student’s speaking ability) is accepted . It means there is a significant effect of the Implementation Multimedia as a Teaching Method to improved the speaking ability of tenth grade at SMA Negeri 5 Pematang Siantar